Family Support & Emotional Intelligence on Burnout Level and Mental Health of Adolescents in School Environment - Lini Maulida; Jarkawi; Sri Ayatina Hayati (ILIN Institute Makassar, 2024)
This study aims to determine (1) whether family support is significantly related to burnout, (2) whether emotional intelligence is significantly related to burnout, (3) whether family support and emotional intelligence are significantly related simultaneously to burnout at SMK Negeri 1 Banjarbaru. This study uses quantitative research uses correlational research. Data collection techniques are carried out by distributing questionnaires. The research sample was carried out using a purposive sampling technique, which included 76 respondents. Data analysis uses multiple correlation. The results of the study indicate that the variable X1 Family Support is significantly related to burnout, so H1 is accepted. The variable X2 Emotional Intelligence is not significantly related to burnout, so H2 is rejected. And based on the simultaneous regression coefficient test, the relationship between family support and emotional intelligence has a significant relationship to burnout, so H3 is accepted.